Foreign Language Anxiety and Its Impact on English Achievement: A Study of Gender Variations in EFL Learners - Aridah; Masruroh, Dzunie; Rusmawaty, Desy (VELES Voices of English Language Education Society, 2025)
Anxiety is a prevalent psychological factor that influences the learning process, particularly in language acquisition, where it can shape students’ confidence, engagement, and overall performance. In contexts where English is learned as a foreign language, anxiety is often linked to students' ability to navigate language learning challenges, affecting both their success and struggles in mastering the language. Understanding the extent of foreign language anxiety and its specific effects is essential, given its potential impact. This study investigates students’ anxiety levels, examines gender differences, and explores the relationship between anxiety and English achievement. A quantitative descriptive survey was conducted with 105 students in Samarinda, Indonesia, using the Foreign Language Classroom Anxiety Scale (FLCA) to measure anxiety and final semester scores to assess achievement. Data analysis using SPSS version 25 revealed that students experienced a high level of foreign language anxiety (M = 3.4459), with female students reporting slightly higher anxiety than males. However, the difference was not statistically significant. Correlation analysis showed a weak negative association (r = -.101, p = .306), suggesting that anxiety had little to no impact on achievement. These findings provide insights into foreign language anxiety in EFL contexts, emphasizing the need for targeted interventions to create a more supportive learning environment and enhance language learning experiences.